Identifikasi dan isolasi promoter gen pembungaan kakao TcLFY Identification and isolation for promoter of TcLFY cacao flowering gene - Djoko SANTOSO; Agustina A. HANDAYAN; Sukarti MOELJOPAWIRO (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2007)
SummaryPromoter is a regulator of geneexpression for a phenotype or trait carried bythe gene. In the structure, a promoter locatedbeyond the 5’ end of the open reading frame ofthe gene on which its expression is regulated.This research aimed to isolate the DNAfragment flanking TcLFY at the 5’ end and toanalyze whether the fragment has charac-teristics of the promoter, primarily the coremotifs of promoter. Using Genome Walkingtechnique, DNA fragments flanking the TcLFYgene at its 5’ end was isolated. Analysis of theDNA sequence was done using onlinecomputer software accessible through web sitewww.softberry.com and an entry sequence ofthe flanking DNA fragment along with the 2.5kb TcLFY sequence. The result indicated thatthe flanking fragment has core motifs for apromoter at proper positions, which are TATAbox at position –80, CAT boxes (CCAAT) at -387 and –626, and GC boxes that are known asUAS were found at the -323 and –537positions. To obtain a conclusive result, thispromoter sequence needs to be furtherexamined to confirm its function.RingkasanPromoter merupakan pengendali ekspresigen untuk memunculkan fenotipe atau karakteryang dibawa oleh gen tersebut. Di dalamstrukturnya, promoter umumnya terletak didaerah ujung 5’ gen yang dikendalikanekspresinya. Tujuan penelitian ini adalahmendapatkan fragmen DNA yang mengapitgen pengendali pembungaan kakao (TcLFY)dan menganalisisnya apakah memilikikarakteristik promoter, yaitu mengandungmotif-motif inti (core motifs) dari promoter.Dengan teknik Genome Walking, fragmenDNA pengapit gen TcLFY di ujung 5’ dapatdiisolasi. Analisis sekuen menggunakanperangkat lunak komputer online (www.softberry.com) dengan input data fragmentersebut ditambah gen TcLFY 2,5 kb dibawahnya, mengindikasikan adanya beberapamotif inti promoter pada posisi yang sesuai,yaitu kotak TATA pada lokasi –80, kotak CAT(CCAAT) di posisi -387 dan –626, dan kotakGC yang merupakan UAS dijumpai padalokasi -323 dan –537. Untuk memperoleh hasilyang bersifat konklusif, sekuen promoter inimasih perlu diuji fungsinya.